An Algorithm Measuring Donor Cell-Free DNA in Plasma of Cellular and Solid Organ Transplant Recipients That Does Not Require Donor or Recipient Genotyping - Gordon, Paul M. K.; Khan, Aneal; Sajid, Umair; Chang, Nicholas; Suresh, Varun; Dimnik, Leo; Lamont, Ryan E.; Parboosingh, Jillian S.; Martin, Steven R.; Pon, Richard T.; Weatherhead, Jene; Wegener, Shelly; et al. (Frontiers in Cardiovascular Medicine, 2016)
Cell-free DNA (cfDNA) has significant potential in the diagnosis and monitoring of clinical conditions but accurately and easily distinguishing the relative proportion of DNA molecules in a mixture derived from two different sources (i.e. donor and recipient tissues after transplantation) is challenging. In human cellular transplantation there is currently no useable method to detect in vivo engraftment and blood-based non-invasive tests for allograft rejection in solid organ transplantation are either non-specific (e.g. creatinine in kidney transplantation, liver enzymes in hepatic transplantation) or absent (i.e. heart transplantation). Elevated levels of donor cfDNA have been shown to correlate with solid organ rejection but complex methodology limits implementation of this promising biomarker. We describe a cost-effective method to quantify donor cfDNA in recipient plasma using a panel of high-frequency single nucleotide polymorphisms, next-generation (semiconductor) sequencing and a novel mixture model algorithm. In vitro, our method accurately and rapidly determined donor/recipient DNA admixture. For in vivo testing, donor cfDNA was serially quantified in an infant with a urea cycle disorder after receiving six daily infusions of donor liver cells. Donor cfDNA isolated from 1-2 ml of recipient plasma was detected as late as 24 weeks after infusion suggesting engraftment. The percentage of circulating donor cfDNA was also assessed in pediatric and adult heart transplant recipients undergoing routine endomyocardial biopsy with levels observed to be stable over time and generally measuring <1% in cases without moderate or severe cellular rejection. Unlike existing non-invasive methods used to define the proportion of donor cfDNA in solid organ transplant patients, our assay does not require sex mismatch, donor genotyping or whole-genome sequencing and potentially has broad application to detect cellular engraftment or allograft injury after transplantation.